2014
DOI: 10.1038/nphys2984
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of steady inertial wave turbulence in deep rotating flows

Abstract: The theoretical framework that should be used for describing rotating turbulence 1-3 is the subject of an active debate. It was shown experimentally 4,5 and numerically 6,7 that the formalism of 2D turbulence is useful in the description of many aspects of rotating turbulence. On the other hand, theoretical and numerical work suggests that the formalism of wave turbulence 8-10 should provide a reliable description of the entire 3D flow field 11-15. The waves that are suggested as the basis for this turbulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 26 publications
8
89
0
Order By: Relevance
“…An interesting fact, that sheds more light on how these mechanisms work, is that these effects are not observed in purely rotating flows [26,43]. While these flows can also generate strong horizontal velocity fields, waves tend to travel in the vertical direction (as compared to the stratified case, where they tend to travel horizontally), and no Doppler shift develops as the waves are perpendicular to the large-scale flow.…”
Section: B Spatio-temporal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting fact, that sheds more light on how these mechanisms work, is that these effects are not observed in purely rotating flows [26,43]. While these flows can also generate strong horizontal velocity fields, waves tend to travel in the vertical direction (as compared to the stratified case, where they tend to travel horizontally), and no Doppler shift develops as the waves are perpendicular to the large-scale flow.…”
Section: B Spatio-temporal Analysismentioning
confidence: 99%
“…As already mentioned, an inverse cascade is a self-similar process by which energy is transferred nonlinearly from small scales to larger scales, so energy gets accumulated in structures with larger correlation length than that of the injection mechanism. Inverse cascades have been ex-tensively studied in two dimensional turbulence [1], and have also been observed in rotating turbulence (including rotating stratified turbulence) [24][25][26]. But results for purely stratified turbulence are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Following [31,32], we analyze how the kinetic energy is located around the dispersion relation of inertial waves given by ω ¼ AE2 cos θ, where ω is the dimensionless frequency, and θ is the angle between the wave vector and the rotation axis. This is achieved by computing the spatiotemporal Fourier transformûðk; ωÞ of the velocity field uðx; tÞ and summing contributions associated with the same angle θ.…”
Section: -2mentioning
confidence: 99%
“…Barker and Lithwick [19], in their local model of the elliptical instability, nonetheless showed that strong geostrophic flows emerge during the saturation and disrupt the inertial wave resonances, leading instead to growth and decay cycles. This competition between dominant geostrophic modes and inertial waves is reminiscent of the duality observed in rotating turbulence where, on one hand, geostrophic flows are widely observed [30], and on the other hand, inertial waves have been shown to survive on top of the turbulent background [31][32][33][34]. Conversely from experiments and numerical simulations of rotating turbulence, where energy is injected arbitrarily into both vortices and inertial waves through an external artificial forcing, the elliptical instability provides a natural mechanism that initially injects energy into a few inertial waves only, whose properties can be theoretically predicted.…”
mentioning
confidence: 99%
See 1 more Smart Citation